Polyacrylonitrile fiber doped high-sulfur iron tailing mortar as well as preparation method and application thereof

By adding polyacrylonitrile fibers to the high-sulfur iron tailing mortar, the problems of volume expansion, structural looseness and strength reduction of high-sulfur tailing mortar during use are solved, which significantly improves its freezing and sulfate corrosion resistance and extends its service life.

CN119841600APending Publication Date: 2025-04-18SHANDONG UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510109696.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

During use, high-sulfur tailings sand can easily lead to volume expansion, structural looseness and strength of the mortar material, and insufficient anti-freeze and sulfate corrosion resistance, which affects the safety and durability of building mortar.

Method used

Polyacrylonitrile fibers are added to the high-sulfur iron tailing mortar, and through its bridging, cracking and filling, the physical and mechanical properties of the mortar and the resistance to sulfate corrosion are improved.

Benefits of technology

It significantly improves the compressive, tensile and flexural properties of high-sulfur tailings mortar, delays strength deterioration, improves the freezing and sulfate corrosion resistance, and extends the service life of the mortar.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119841600A_ABST
    Figure CN119841600A_ABST
Patent Text Reader

Abstract

The invention discloses polyacrylonitrile fiber doped high-sulfur iron tailing mortar as well as a preparation method and application thereof. The high-sulfur iron tailing mortar is prepared from the following raw material components in parts by weight: 1500 to 1600 parts of cement, 2300 to 2400 parts of standard sand, 2300 to 2400 parts of high-sulfur iron tailings, 5 to 6 parts of polyacrylonitrile fiber, 7 to 8 parts of a polycarboxylic acid water reducing agent and 600 to 700 parts of water. In the invention, the polyacrylonitrile fiber can bridge cracks of the high-sulfur iron tailing mortar and prevent the formation and expansion of the cracks. In addition, the polyacrylonitrile fibers are small in diameter and can play a role in filling micropores. Therefore, the polyacrylonitrile fiber not only effectively improves the long-age performance of the mortar, but also obviously enhances the frost resistance and sulfate erosion resistance, and greatly improves the safety and durability of the iron tailing mortar. Meanwhile, the preparation cost is low, and secondary utilization of solid waste is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of resource utilization of high-sulfur tailings, and in particular to a polyacrylonitrile fiber-doped high-sulfur iron tailings mortar and a preparation method and application thereof. Background Art

[0002] With the booming construction industry, river sand is mined in large quantities as an important building material. Due to long-term over-exploitation of river sand in many areas, the river ecosystem has been destroyed. At the same time, river sand resources are facing depletion in some places and it is difficult to meet the growing demand of the construction industry. Moreover, people's awareness of ecosystem protection is constantly increasing, and the government has also strengthened supervision of river sand mining. Many places have introduced policies to restrict river sand mining, which makes the construction industry's need to find river sand substitutes more urgent.

[0003] With the continuous development of the mining industry, the discharge of iron tailings is increasing. Iron tailings contain a large amount of solid waste and occupy a large amount of land resources. High-sulfur iron tailings are a type of iron tailings. Their storage not only wastes land, but also may cause potential pollution to the surrounding soil, water and other ecological environments due to the migration of harmful substances (such as sulfur) in them. Government departments have issued relevant environmental protection policies to encourage enterprises to make rational use of industrial waste residues such as iron tailings to reduce damage to the environment. Moreover, the particle size distribution and chemical composition of high-sulfur iron tailings are similar to those of river sand to a certain extent. Through proper processing, high-sulfur iron tailings can meet the requirements of building materials for the physical properties of fine aggregate.

[0004] When high-sulfur iron tailings are used as mortar aggregate, the sulfides (such as pyrite, etc.) in the high-sulfur iron tailings are easily oxidized after contact with air and water. Sulfate ions will further react with the hydration products of cement to form gypsum (CaSO4·2H2O) and ettringite (AFt). The specific chemical reaction is as follows: ① Oxidation of sulfur 2FeS2+7O2+2H2O=2Fe 2+ +4SO4 2- +4H + ②Formation of gypsum Ca(OH)2+SO4 2- +2H2O=CaSO4·2H2O+OH - ③Formation of AFt 3CaO·Al2O3+3(CaSO4·2H2O)+26H2O=3CaO·Al2O3·3CaSO4·32H2O(AFt) 3CaO·Al2O3·6H2O+3(CaSO4·2H2O)+20H2O=3CaO·Al2O3·3CaSO4·32H2O(AFt) During the long-term use of mortar materials, gypsum (CaSO4·2H2O) and calcium sulfoxide (AFt) will cause the volume expansion of mortar materials. This expansion will generate internal stress, resulting in cracking and peeling of the mortar. In addition, the acidic substances generated by sulfur oxidation will also corrode the hydration products, resulting in loose mortar structure and reduced strength. These two negative effects seriously affect the safety and durability of building mortar structures. When the existing technology uses high-sulfur tailings as aggregate, the effect of suppressing the negative effects of sulfides on mortar materials is limited. In addition, the preparation of building mortar with high-sulfur iron tailings not only reduces production costs but also protects the ecological environment.

[0005] The area of ​​seasonal frozen ground in my country is about 5.137 million km 2 , accounting for about 53.5% of the country's land area. The mortar materials in this area are prone to cracking and surface peeling under the action of freeze-thaw cycles. This is because when the pore water inside the mortar freezes, the volume expands by about 9%. The expansion pressure generated by the ice crystals will cause tiny cracks on the mortar surface. As the number of freeze-thaw cycles increases, these cracks gradually expand and connect, causing the mortar surface to peel off. For mortar materials that have experienced freeze-thaw cycles, the cost of repair or reconstruction is high. Therefore, from the perspective of safety and economy, it is very necessary to study a mortar structure with high frost resistance. In tailings mortar materials, its own structure and composition are relatively complex. Factors such as the particle shape, grading, and impurities contained in the tailings themselves will affect the effect of the antifreeze agent. Therefore, the effect of adding antifreeze agents to tailings mortar materials to improve the antifreeze performance is limited.

[0006] The area of ​​saline land in my country is about 991,300 km 2 , accounting for about 10% of the country's total land area. High-sulfur tailings contain a certain amount of sulfide. When encountering external sulfate erosion, the two parts of sulfate will react with the hydration products in the mortar to form gypsum and calcium aluminate. This internal and external sulfate coupling erosion will produce huge internal stress inside the mortar, causing cracks in the mortar. As the cracks continue to develop, the structural integrity of the mortar is destroyed, the strength is reduced, and eventually the structure may fail. At present, some studies have used sulfur-resistant cement or chemical admixtures to resist sulfate erosion, but the effect is very limited.

[0007] Therefore, how to solve the problems of irregular cracking of mortar, poor frost resistance and reduced sulfate corrosion resistance caused by high-sulfur tailings is still a difficulty in the development of high-sulfur tailings resource utilization technology. Polyacrylonitrile fiber can be added to high-sulfur tailings mortar to improve durability. The fiber can form a dense spatial skeleton structure in the mortar, and the bonding force between the fiber and the cement matrix is ​​very strong, which can also effectively delay the long-term strength degradation. Therefore, the development of a method that can utilize high-sulfur iron tailings on a large scale and improve the long-term physical and mechanical properties of high-sulfur tailings mortar has opened up a new way for the resource utilization of high-sulfur iron tailings. Summary of the invention

[0008] In view of the defects and problems of the prior art, the present invention provides a high-sulfur iron tailings mortar doped with polyacrylonitrile fibers, and a preparation method and application thereof. Specifically, the present invention relates to a method for preparing high-sulfur iron tailings mortar using high-sulfur iron tailings and polyacrylonitrile fibers. By adding an appropriate amount of polyacrylonitrile fibers that play a bridging, crack-blocking and filling role to the high-sulfur tailings mortar, the long-term physical and mechanical properties of the high-sulfur tailings mortar are improved.

[0009] A polyacrylonitrile fiber-doped high-sulfur iron tailings mortar comprises the following components: by weight, 1500-1600 parts of cement, 2300-2400 parts of standard sand, 2300-2400 parts of high-sulfur iron tailings, 5-6 parts of polyacrylonitrile fibers, 7-8 parts of polycarboxylic acid water reducer, and 600-700 parts of water.

[0010] Preferably, the cement has a P·O 42.5, an initial setting time of 230 minutes, a final setting time of 300 minutes, a magnesium oxide content of 2.66%, a loss on ignition of 3.73%, and a specific surface area of ​​351 m² / kg.

[0011] Preferably, the standard sand has a quartz content greater than 98%, a water content less than 0.18%, a mud content less than 0.18%, a loss on ignition less than 0.47%, and a fineness modulus of 2.38.

[0012] Preferably, the high-sulfur iron tailings has a quartz content of 24.7%, a sulfur trioxide content of 15.06%, and a fineness modulus of 1.54.

[0013] Preferably, the polyacrylonitrile fiber has a length of 12 mm, a diameter of 13 μm, and a density of 1.18 g / cm 3 , the tensile strength is 530MPa, the elastic modulus is 7.2GPa, and the ultimate elongation is 22%.

[0014] Preferably, the polycarboxylate water-reducing agent has a water reduction rate of 46%, a water bleeding rate of 22%, and a sodium sulfate content of 0.6%.

[0015] The present invention also provides a method for preparing the polyacrylonitrile fiber reinforced high-sulfur iron tailings mortar, comprising the following steps: (1) Place the high-sulfur iron tailings and standard sand in a blast drying oven at 105±2℃ and dry them to constant weight. After cooling to room temperature, use a standard vibrating screen to sieve them. (2) Mix the high-sulfur iron tailings and standard sand for 1 minute until the particles are evenly distributed; then, add cement and mix for 1 minute, and then add polyacrylonitrile fiber and mix for 2 minutes until the particles are evenly distributed; (3) adding water and polycarboxylate water reducer, and stirring with a hand-held mixer for 5 minutes to obtain a mixture; (4) The mixture after stirring in step (3) is manually stirred for 10 to 25 seconds until it is evenly distributed, thereby obtaining a fiber-reinforced high-sulfur iron tailings mortar.

[0016] Preferably, the stirring for 5 minutes in step (3) comprises stirring at a low speed of 135 r / min for 2 minutes and stirring at a high speed of 270 r / min for 3 minutes.

[0017] Compared with the prior art, the present invention has the following advantages: 1. The present invention incorporates polyacrylonitrile fiber into the high-sulfur tailings mortar, which plays a strong bridging role and crack-resisting role, making the stress distribution inside the mortar more uniform. In addition, polyacrylonitrile fiber can play a filling effect, effectively fill the pores of the mortar and optimize the microstructure inside the mortar. After a long curing period, the porosity inside the polyacrylonitrile fiber-reinforced high-sulfur tailings mortar is significantly reduced, and the number of harmful pores is significantly reduced. Moreover, the compression, tension and flexural properties of the high-sulfur tailings mortar under long-term aging will be damaged by sulfur corrosion. The addition of polyacrylonitrile fiber greatly reduces the risk of late cracking of high-sulfur tailings, effectively delays the oxidation rate of pyrite inside the high-sulfur tailings mortar, reduces the number of sulfate radicals, and greatly improves the sulfate corrosion resistance inside the high-sulfur tailings mortar, improves the density and strength of the high-sulfur tailings mortar, and thus extends the service life of the high-sulfur tailings mortar.

[0018] 2. The polyacrylonitrile fiber reinforced high-sulfur tailings mortar prepared by the present invention has good frost resistance. When the high-sulfur tailings mortar is in a freeze-thaw environment, the water in the pores will freeze and expand in volume. The polyacrylonitrile fibers form a three-dimensional network structure inside the mortar, and these fibers can provide a certain buffer space for the expansion of ice crystals. Ice crystals will squeeze the fibers during the expansion process, and the fibers can absorb part of the expansion pressure through their own elastic deformation, reducing the damage to the mortar matrix. In addition, the presence of fibers can also prevent the expansion of microcracks caused by the expansion of ice crystals. During the freeze-thaw cycle, the expansion of microcracks is one of the key factors that lead to the decrease in the frost resistance of the mortar. Polyacrylonitrile fibers can bind the edges of the cracks like a "bandage" to prevent the cracks from expanding continuously due to repeated freeze-thaw effects, thereby improving the frost resistance of the mortar. At the same time, polyacrylonitrile fibers can reduce the migration rate of water inside the mortar. During the freeze-thaw cycle, the migration of water will cause the pore water content in the local area to increase, aggravating freeze-thaw damage. The addition of fibers makes the pore channels inside the mortar more tortuous, slowing down the flow of water in the pores, allowing the mortar to maintain a relatively stable internal humidity environment during freeze-thaw cycles and reducing damage caused by moisture migration.

[0019] 3. The polyacrylonitrile fiber reinforced high-sulfur iron tailings mortar prepared by the present invention has a good effect on resisting internal and external sulfate coupling erosion. Polyacrylonitrile fiber can play a role in blocking sulfate intrusion and delaying internal sulfide oxidation in high-sulfur tailings mortar. The network structure formed by the fibers interweaving inside the mortar can increase the path length and difficulty of sulfate diffusion. Sulfate needs to bypass the fiber to enter the deeper area inside the mortar, which reduces the reaction probability of sulfate and cement hydration products in the mortar. At the same time, the fiber can fill the pores of the mortar and reduce the channel for sulfate invasion. Good impermeability can effectively prevent the penetration of sulfate solution in the mortar, thereby reducing the degree of sulfate erosion on the mortar. Moreover, when sulfate reacts with the components in the mortar, expansive products (such as gypsum and calcium aluminate) are produced, resulting in damage to the internal structure of the mortar. The bridging effect of polyacrylonitrile fiber can inhibit the damage caused by this expansion to a certain extent. Even in the case of the generation of expansive products, the fiber can maintain the relative integrity of the internal structure of the mortar, reduce the generation and expansion of cracks, and improve the mortar's resistance to internal and external sulfate coupling erosion.

[0020] 4. The method for preparing polyacrylonitrile fiber reinforced high-sulfur iron tailings mortar provided by the present invention has a wide source of materials, a simple production process, and makes extensive use of industrial solid waste high-sulfur tailings. The polyacrylonitrile fiber selected by the present invention has the advantages of high performance, low cost, and green environmental protection. Therefore, the present invention not only saves production costs and can reduce the amount of river sand in the mortar, but also realizes the secondary utilization of waste, and has significant economic benefits, social benefits, and environmental benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 It is a schematic diagram comparing the porosity of mortar samples of the embodiment of the present invention and the comparative example; Figure 2 It is a schematic diagram comparing the longitudinal wave velocities of the mortar samples of the embodiment of the present invention and the comparative example; Figure 3 It is a schematic diagram comparing the compressive strength of mortar samples of the embodiment of the present invention and the comparative example; Figure 4 It is a schematic diagram comparing the tensile strength of mortar samples of the embodiment of the present invention and the comparative example; Figure 5 It is a schematic diagram comparing the flexural strength of mortar samples of the embodiment of the present invention and the comparative example. DETAILED DESCRIPTION

[0022] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0023] Example 1 A polyacrylonitrile fiber reinforced high-sulfur tailings mortar (named: B0P0.08), including the following raw material components in parts by weight: 1560 parts of cement, 2340 parts of standard sand, 2340 parts of high-sulfur iron tailings, 5.5 parts of single-doped polyacrylonitrile fiber, 7.8 parts of polycarboxylic acid water reducer, and 655 parts of water.

[0024] The method for preparing the polyacrylonitrile fiber reinforced high-sulfur tailings mortar comprises the following steps: (1) The high-sulfur iron tailings and standard sand were placed in a blast drying oven at 105°C and dried to constant weight, cooled to room temperature, and sieved using a standard vibrating screen; the standard sand had a quartz content greater than 98%, a moisture content less than 0.18%, a mud content less than 0.18%, a loss on ignition less than 0.47%, and a fineness modulus of 2.38; the high-sulfur iron tailings had a quartz content of 24.7%, a sulfur trioxide content of 15.06%, and a fineness modulus of 1.54; (2) Mix the high-sulfur iron tailings and standard sand for 1 minute until the particles are evenly distributed; then, add cement and mix for 1 minute, then add polyacrylonitrile fiber and mix for 2 minutes until the particles are evenly distributed; the cement has a P·O 42.5, an initial setting time of 230 minutes, a final setting time of 300 minutes, a magnesium oxide content of 2.66%, a loss on ignition of 3.73%, and a specific surface area of ​​351 m² / kg; the polyacrylonitrile fiber has a length of 12 mm, a diameter of 13 μm, and a density of 1.18 g / cm 3 , tensile strength is 530MPa, elastic modulus is 7.2GPa, and ultimate elongation is 22%; (3) adding water and polycarboxylate water reducer, and stirring for 5 minutes with a hand-held mixer to obtain a mixture, wherein the water reduction rate of the polycarboxylate water reducer is 46%, the water bleeding rate is 22%, and the sodium sulfate content is 0.6%; the stirring for 5 minutes is stirring at a low speed of 135 r / min for 2 minutes and stirring at a high speed of 270 r / min for 3 minutes; (4) The mixture after stirring in step (3) is manually stirred for 10 to 25 seconds to obtain polyacrylonitrile fiber reinforced high-sulfur iron tailings mortar.

[0025] Comparative Example 1 This comparative example provides a high-sulfur tailings mortar (named: B0P0), comprising the following raw material components in parts by weight: 1560 parts of cement, 2340 parts of standard sand, 2340 parts of high-sulfur iron tailings, 7.8 parts of polycarboxylic acid water reducer, and 655 parts of water.

[0026] The preparation method of the high-sulfur tailings mortar comprises the following process steps: (1) The tailings and standard sand are placed in a blast drying oven at 105±2°C and dried to constant weight, and then cooled to room temperature and sieved using a standard vibrating screen; the standard sand has a quartz content greater than 98%, a moisture content less than 0.18%, a mud content less than 0.18%, a loss on ignition less than 0.47%, and a fineness modulus of 2.38; the high-sulfur iron tailings has a quartz content of 24.7%, a sulfur trioxide content of 15.06%, and a fineness modulus of 1.54; (2) Mix the high-sulfur iron tailings and standard sand for 1 minute until the particles are evenly distributed; then, add cement and mix for 1 minute. The cement has a P·O 42.5, an initial setting time of 230 minutes, a final setting time of 300 minutes, a magnesium oxide content of 2.66%, a loss on ignition of 3.73%, and a specific surface area of ​​351 m² / kg; (3) Add water and polycarboxylate water reducer, and stir with a handheld mixer for 5 minutes, including 2 minutes of low-speed stirring at 135 r / min and 3 minutes of high-speed stirring at 270 r / min; (4) The mixture after stirring in step (3) is manually stirred for 10 to 25 seconds until it is uniformly mixed, thereby obtaining high-sulfur iron tailings mortar.

[0027] Test example In order to demonstrate the long-term performance, resistance to freeze-thaw cycle damage and resistance to internal and external sulfate corrosion of the iron tailings mortar prepared in the embodiment of the present invention (adding 0.08% polyacrylonitrile fiber) and the comparative example (no fiber), the mortar samples prepared in the comparative example and the embodiment are analyzed below.

[0028] Test 1: The hardened specimens were cured in a standard curing box (20±2℃, ≥95RH%) for 28 days and 120 days, and then performance tests were conducted to ensure that they met the building requirements.

[0029] Test 2: The hardened specimens were cured in a standard curing box (20±2℃, ≥95RH%) for 26 days, then dried at 65±5℃ for 48h, and finally cooled to room temperature before the sulfate dry-wet cycle corrosion test.

[0030] The sulfate dry-wet cycle erosion test was carried out in accordance with JTG 3420-2020 "Test Procedures for Cement and Cement Concrete for Highway Engineering". The number of dry-wet cycles in the test was set to 15, 30, 45, 60, 75, and 90 times. The specific steps are: immersion in water (5% sodium sulfate solution) for 15 hours → natural air drying (25°C) for 1 hour → oven drying (65°C) for 6 hours → cooling to room temperature for 2 hours. The dry-wet cycle test was carried out in this order, and the total time for one cycle was 24 hours.

[0031] Test 3: The hardened specimens were cured in a standard curing box (20±2℃, ≥95RH%) for 24 days, then immersed in water for 4 days, and then subjected to freeze-thaw tests after being fully saturated.

[0032] The freeze-thaw cycle test was conducted in accordance with GB / T50082-2009 "Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete". The instrument used in the test was the TMS 9018-R40 freeze-thaw test system, with the freezing temperature set at -20°C, the melting temperature set at 20°C, and the freeze-thaw time of each cycle set at 6h. The number of freeze-thaw cycles was set at 25, 50, 75, and 100 times.

[0033] According to the Chinese standard JTG 3420-2020 "Test Procedure for Cement and Cement Concrete for Highway Engineering" and GB / T50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete", the porosity, longitudinal wave velocity, compressive strength, splitting tensile strength and flexural strength of iron tailings mortar samples were tested. The results are as follows: Figures 1 to 5 shown.

[0034] 1. Adding polyacrylonitrile fiber to high-sulfur iron tailings significantly reduces the porosity of high-sulfur iron tailings mortar, increases longitudinal wave velocity, compressive strength, splitting tensile strength and flexural strength, and optimizes the microscopic pore structure. For example, the 120-day porosity of the comparative example and the embodiment is 24.37% and 21.03%, respectively. Compared with the comparative example, the 120-day compressive strength of the embodiment decreased by 13.71%. For another example, the 120-day compressive strength of the comparative example and the embodiment is 21.42MPa and 27.17MPa, respectively. Compared with the comparative example, the 120-day compressive strength of the embodiment is increased by 26.84%. Adding polyacrylonitrile fiber to high-sulfur tailings mortar can play a significant bridging and crack-blocking role, and improve the compression, tensile and flexural properties of tailings mortar under long curing age. Moreover, the filling effect of polyacrylonitrile fiber significantly reduces the porosity of tailings mortar, sharply reduces the number of harmful pores, and effectively optimizes the microstructure of mortar. The addition of polyacrylonitrile fiber greatly reduces the risk of late cracking of high-sulfur tailings mortar, enhances structural stability and reliability, and lays a solid foundation for the long-term application of high-sulfur tailings mortar in engineering.

[0035] 2. The high frost resistance polyacrylonitrile fiber reinforced iron tailings mortar material sample prepared by adding polyacrylonitrile fiber in the embodiment has good frost resistance. The addition of polyacrylonitrile fiber to the iron tailings mortar significantly reduces the degradation effect of freeze-thaw cycles on the porosity, longitudinal wave velocity, strength and microscopic pore structure of the iron tailings mortar. For example, the porosity increase rate after 0 freeze-thaw cycles and 100 freeze-thaw cycles of the comparative example and the embodiment is 15.22% and 9.51%, respectively. For example, the compressive strength after 100 freeze-thaw cycles of the comparative example and the embodiment is 18.24MPa and 22.28MPa, respectively. The addition of polyacrylonitrile fiber to the iron tailings mortar exerts a strong bridging and crack-blocking effect, and compacts the microstructure inside the mortar. After 100 freeze-thaw cycles, compared with the sample without fiber addition, the porosity inside the polyacrylonitrile fiber reinforced iron tailings mortar decreased significantly, and the number of harmful pores was significantly reduced. Moreover, the deterioration trend of the compression, tension and flexural properties of the tailings mortar is delayed, greatly reducing the risk of cracking of the iron tailings mortar after freeze-thaw cycles.

[0036] 3. The polyacrylonitrile fiber reinforced high-sulfur iron tailings mortar material sample prepared by adding polyacrylonitrile fiber in the embodiment has good resistance to internal and external sulfate coupling erosion. The addition of polyacrylonitrile fiber to the high-sulfur iron tailings mortar significantly reduces the degradation effect of sulfate dry-wet cycles on the porosity, longitudinal wave velocity, strength and microscopic pore structure of the iron tailings mortar. For example, the porosity increase rate after 0 dry-wet cycles and 90 dry-wet cycles of the comparative example and the embodiment is 7.25% and 3.55%, respectively. For example, the compressive strength after 90 dry-wet cycles of the comparative example and the embodiment is 19.37MPa and 23.13MPa, respectively. The addition of polyacrylonitrile fiber to the high-sulfur iron tailings mortar can bridge cracks and fill pores, and optimizes the microstructure inside the mortar to a large extent. After 90 dry-wet cycles, compared with the sample without fiber addition, the porosity inside the polyacrylonitrile fiber reinforced iron tailings mortar decreased significantly, and the number of harmful pores was significantly reduced. Moreover, the deterioration trend of the compression, tension and flexural properties of the tailings mortar is delayed, greatly reducing the risk of cracking of the iron tailings mortar after dry-wet cycles. Moreover, when expansion stress caused by secondary gypsum and calcium aluminate appears inside the fiber-reinforced tailings mortar, the fiber can bear a certain stress and limit a certain micro-deformation, thereby reducing the increase of porosity, improving the density and strength of the high-sulfur iron tailings mortar, and thus extending the service life of the high-sulfur iron tailings mortar.

[0037] From the above results, it can be seen that the density and strength of the iron tailings mortar provided by the present invention are significantly increased after the addition of polyacrylonitrile fiber, which effectively improves the long-term performance, frost resistance and sulfate corrosion resistance, thereby achieving the purpose of improving the safety and durability of the iron tailings mortar, and the preparation cost is low, thereby realizing the secondary utilization of solid waste.

Claims

1. A polyacrylonitrile fiber-doped high-sulfur iron tailings mortar, characterized in that: The invention comprises the following ingredients: by weight, 1500-1600 parts of cement, 2300-2400 parts of standard sand, 2300-2400 parts of high-sulfur iron tailings, 5-6 parts of polyacrylonitrile fiber, 7-8 parts of polycarboxylic acid water reducer and 600-700 parts of water.

2. The high-sulfur iron tailings mortar according to claim 1, characterized in that: The cement has a P·O 42.5, an initial setting time of 230 minutes, a final setting time of 300 minutes, a magnesium oxide content of 2.66%, a loss on ignition of 3.73%, and a specific surface area of ​​351 m² / kg.

3. The high-sulfur iron tailings mortar according to claim 1, characterized in that: The standard sand has a quartz content greater than 98%, a water content less than 0.18%, a mud content less than 0.18%, a loss on ignition less than 0.47%, and a fineness modulus of 2.

38.

4. The high-sulfur iron tailings mortar according to claim 1, characterized in that: The high-sulfur iron tailings has a quartz content of 24.7%, a sulfur trioxide content of 15.06%, and a fineness modulus of 1.

54.

5. The high-sulfur iron tailings mortar according to claim 1, characterized in that: The polyacrylonitrile fiber has a length of 12 mm, a diameter of 13 μm, and a density of 1.18 g / cm 3 , the tensile strength is 530MPa, the elastic modulus is 7.2GPa, and the ultimate elongation is 22%.

6. The high-sulfur iron tailings mortar according to claim 1, characterized in that: The polycarboxylate water reducer has a water reduction rate of 46%, a water bleeding rate of 22%, and a sodium sulfate content of 0.6%.

7. The method for preparing high-sulfur iron tailings mortar according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) Place the high-sulfur iron tailings and standard sand in a blast drying oven at 105±2℃ and dry them to constant weight. After cooling to room temperature, use a standard vibrating screen to sieve them. (2) Mix the high-sulfur iron tailings and standard sand for 1 minute until the particles are evenly distributed; then, add cement and mix for 1 minute, and then add polyacrylonitrile fiber and mix for 2 minutes until the particles are evenly distributed; (3) adding water and polycarboxylate water reducer, and stirring with a hand-held mixer for 5 minutes to obtain a mixture; (4) The mixture after stirring in step (3) is manually stirred for 10 to 25 seconds until it is evenly distributed, thereby obtaining a fiber-reinforced high-sulfur iron tailings mortar.

8. The preparation method according to claim 7, characterized in that The stirring for 5 minutes in step (3) is performed by stirring at a low speed of 135 r / min for 2 minutes and stirring at a high speed of 270 r / min for 3 minutes.

9. Use of the high-sulfur iron tailings mortar as described in any one of claims 1 to 6 in the preparation of building wall materials, ground materials, and road base materials.

10. Use of the high-sulfur iron tailings mortar obtained by the preparation method according to claim 7 or 8 in the preparation of building wall materials, ground materials, and road base materials.

Citation Information

Patent Citations

  • Method for preparing tailing fiber cement mortar from basalt fibers

    CN117756465A